CLASSROOM FACTORS AND LANGUAGE LEARNING ANXIETY: 2019-2024 BIBLIOMETRIC REVIEW - Andini, Zendy Dwi; Rohmah, Zuliati; Abdullah, Nur Nabilah (Universitas Islam Negeri Sunan Gunung Djati, 2025)
Language learning anxiety has long been recognized as a significant challenge to students’ language acquisition, with classroom dynamics playing a critical role. This study examined how such factors influenced language learning anxiety between 2019 and 2024, with particular attention to the impact of the COVID-19 pandemic. Using bibliometric analysis, the study reviewed over 150 publications to identify key research trends, influential works, and major contributors in the field of language education. The analysis revealed a 40% increase in studies focusing on classroom-related anxiety during the review period and highlighted a growing interest in how technology shapes students’ emotional experiences. Findings indicated that supportive classroom environments, characterized by positive teacher-student interactions and strong peer support, were associated with reduced anxiety. The shift to online and hybrid learning introduced both benefits and challenges: while technology facilitated communication for some students, it increased anxiety for others. Despite growing research attention, studies remained fragmented, often examining classroom factors in isolation rather than as interconnected elements. This review offers valuable insights for educators and policymakers, highlighting the need for holistic strategies that promote inclusive and emotionally supportive learning environments. The findings also lay a foundation for future research aimed at reducing language learning anxiety and improving student outcomes across diverse educational contexts.